Invasive species influence macroinvertebrate biomonitoring tools and functional diversity in British rivers. Issue 1 (4th December 2020) - Guareschi, Simone; Laini, Alex; England, Judy; Johns, Tim; Winter, Martin; Wood, Paul J.
Abstract: Biological invasions could have major implications for the management and conservation of freshwater systems if they lead to a misclassification of waterbodies. However, there is limited understanding of the sensitivity of existing biomonitoring tools to invasive species in rivers; and even less known regarding how they influence community taxonomic and functional measures. This research explores the response of freshwater macroinvertebrate communities to biological invasion using taxonomic and functional indices. Utilising a long‐term dataset (spanning 2000–2019, 5, 988 samples) from rivers in England, the performance of four biomonitoring tools (WHPT, WHPT‐ASPT, LIFE and PSI) and two community functional indices (functional richness and redundancy) was examined before and after the colonisation of the invasive species, Dikerogammarus haemobaphes (Eichwald, 1841; Crustacea: Gammaridae). This species represents a recent (first record 2012) and highly successful invader, allowing its range expansion within waterbodies to be examined in detail. Spatial (national and basin level) and seasonal (spring and autumn) effects were investigated using a before–after control–impact (BACI) experimental framework and linear mixed effects models. Results indicated that invasion by D. haemobaphes resulted in significant reductions to the WHPT index and functional diversity metrics (richness and redundancy) while more subtle patterns were observed for other metrics. Analysis of seasonal and individual river basins (River Trent and R. Thames) identified largely consistent responses. The establishment of D. haemobaphes also resulted in some modifications to the functional composition of aquatic communities primarily associated with voltinism and resistance features. Synthesis and applications . Our findings indicate that Dikerogammarus haemobaphes should be considered a significant pressure to riverine communities. These results have implications for biomonitoring, which informs managerial actions as effects may not be detected using a single taxonomic index. Community functional measures are useful in characterising the effects of invasive species and may form a valuable part of the 'toolbox' used for studying biological invasions in rivers. The research illustrates the need to consider the wider threats posed by invasive species on the long‐term integrity of freshwaters and the efficacy of freshwater biomonitoring tools. Abstract : Our findings indicate that Dikerogammarus haemobaphes should be considered a significant pressure to riverine communities. These results have implications for biomonitoring, which informs managerial actions as effects may not be detected using a single taxonomic index. Community functional measures are useful in characterising the effects of invasive species and may form a valuable part of the 'toolbox' used for studying biological invasions in rivers. The research illustrates the need to consider the wider threats posed by invasive species on the long‐term integrity of freshwaters and the efficacy of freshwater biomonitoring tools. Resumen: Las invasiones biológicas pueden tener importantes repercusiones en la gestión y conservación de los ecosistemas fluviales si dan lugar a clasificaciones erróneas del estado de los cuerpos de agua. Sin embargo, el conocimiento de la sensibilidad de las herramientas de biomonitoreo frente a las especies invasoras en ríos, así como su influencia sobre las métricas taxonómicas y funcionales de la comunidad, es todavía limitado. Esta investigación explora la respuesta de las comunidades de macroinvertebrados acuáticos a las invasiones biológicas utilizando índices taxonómicos y funcionales. Utilizando un conjunto de datos a largo plazo de ríos de Inglaterra (desde 2000 a 2019, con 5, 988 muestras), se examinó la respuesta de cuatro métricas de biomonitoreo (WHPT, WHPT‐ASPT, LIFE, PSI) y dos índices funcionales (riqueza funcional y redundancia) antes y después del establecimiento de Dikerogammarus haemobaphes (Eichwald, 1841; Crustacea: Gammaridae), un invasor reciente en los ríos de Inglaterra (primera cita en 2012). Se investigaron los efectos espaciales (a nivel nacional y de cuenca) y estacionales utilizando un diseño experimental 'BACI' y modelos lineales mixtos. Los resultados muestran que la invasión de D. haemobaphes provoca descensos significativos del índice WHPT y de las métricas de diversidad funcional, mientras que se observan patrones más sutiles en otras métricas. El análisis de los datos por cuencas (Trent y Thames) y por estación (primavera y otoño) identificó respuestas consistentes en gran medida. El establecimiento de D. haemobaphes dio lugar también a algunas modificaciones en la composición funcional de las comunidades, asociadas principalmente a los rasgos biológicos de voltinismo y formas de resistencia. Estos resultados muestran que el establecimiento de poblaciones de D. haemobaphes puede considerarse como una presión significativa para las comunidades fluviales. Estos resultados tendrían implicaciones para el biomonitoreo y la gestión, ya que es posible que los efectos de la invasión no se detecten utilizando únicamente índices taxonómicos. Así, las métricas funcionales de la comunidad resultan de utilidad en la caracterización de los efectos de las especies invasoras, debiendo formar parte de la 'caja de herramientas' utilizada para estudiar las invasiones biológicas en ríos. Esta investigación ilustra la necesidad de considerar, en sentido amplio, las amenazas que representan las especies invasoras sobre la integridad de los ecosistemas fluviales a largo plazo, así como la eficacia de las diferentes herramientas de biomonitoreo.